2022
DOI: 10.3390/insects13020205
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Screening of Mexican, Rwandan and Commercial Entomopathogenic Nematodes to Be Used against Invasive Fall Armyworm, Spodoptera frugiperda

Abstract: The fall armyworm (FAW), Spodoptera frugiperda Smith (Lepidoptera: Noctuidae) is an important pest of maize originating from the Americas. It recently invaded Africa and Asia, where it causes severe yield losses to maize. To fight this pest, tremendous quantities of synthetic insecticides are being used. As a safe and sustainable alternative, we explore the possibility to control FAW with entomopathogenic nematodes (EPN). We tested in the laboratory whether local EPNs, isolated in the invasive range of FAW, ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 49 publications
2
18
0
Order By: Relevance
“…The type hosts are unknown as the nematodes of this genus can be hosted by different insect species ( Yan et al, 2016 ; Kajuga et al, 2018 ; Fallet et al, 2022 ) and were isolated from mixed soil samples by the Galleria baiting technique ( White, 1927 ; Bedding and Akhurst, 1975 ). Briefly, S. africanum n. sp.…”
Section: Resultsmentioning
confidence: 99%
“…The type hosts are unknown as the nematodes of this genus can be hosted by different insect species ( Yan et al, 2016 ; Kajuga et al, 2018 ; Fallet et al, 2022 ) and were isolated from mixed soil samples by the Galleria baiting technique ( White, 1927 ; Bedding and Akhurst, 1975 ). Briefly, S. africanum n. sp.…”
Section: Resultsmentioning
confidence: 99%
“…As FAW larvae are above-ground pests, they rarely encounter soil-borne EPN and are therefore poorly adapted to resist them. This may explain why the caterpillars have been found to be highly susceptible to many species and strains of EPN (Acharya et al, 2020; Fallet et al, in press). EPN normally only reproduce inside an insect host, but they can also be mass produced in fermenters with cultures of their specific symbiotic bacteria or in semi-solid cultures.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, infection for 24 h was enough to cause the 100% mortality of S. frugiperda at a concentration of 250 IJs per 5th stage larva. Although it has been reported that H. bacteriophora was virulent in many insect species, including S. frugiperda , its virulence and killing speed varied among strains within EPN species [ 41 ]. For instance, H. bacteriophora collected from Daedong Tech (Daegu, Korea) caused ~60% mortality in 3rd instar larvae and ~50% mortality in 5th instar larvae at a concentration of 50 IJs per larva for 72 h post-treatment [ 26 ].…”
Section: Discussionmentioning
confidence: 99%